Usability and Acceptability of SinoBed Mobile App for Pressure Ulcer Prevention Among Stroke Patients - Lindayani, Linlin; Juliasry, Dheani; Taryudi, Taryudi; Mutiar, Astri; Al Freadman Koa, Apriyadno Jose; Darmawati, Irma (Jurnal Pendidikan Keperawatan Indonesia, 2024)
Introduction: The ever-increasing adoption of smartphones globally has led to an increase in the use of apps for a wide array of health issues, resulting in favorable outcomes. Mobile apps can provide an easy and efficient method to track wound progression, such as pressure ulcers, using easy-to-use tools that organize information chronologically and visually. Objective: The purpose of this study was to evaluate the perceived utility, acceptability and satisfaction of potential users with a program aimed at reducing the severity of pressure sores in stroke patients. Methods: A quantitative approach was used in this study, with a sample size of 30 people. Users evaluate the usability of the application after the application is shared and ready to use. Results: The usability and acceptance test consisted of 30 participating end users; 76.7% of them were female and 23.3% were male. Their average age was 30.9 years (SD=7.71). Completed two post-task questionnaires. With the average usability score of the total score value assuming the range of 0-100, a value of 85.25 (SD=5.92) was obtained, indicating that most of the data gathered relatively close to the mean, indicating that the Sinobed application is already in the acceptable category with a grade scale of A (Excellent) which indicates that the score is relatively good with a minimum value of 75 and a maximum value of 97.5. Thus, the average acceptance score of the total score of the mean (average) value of 94.32 and standard deviation (SD = 4.65), this result indicates that the majority of respondents tend to agree. Conclusion: The SinoBed app has great potential in supporting decubitus prevention in stroke patients in the digital era. Features such as automatic mobilization repositioning, repositioning time reminders, and temperature, humidity, and weight monitoring are considered very useful and helpful in facilitating patient care. Integration of the app with hospital SOPs can also expand the scope of decubitus prevention and ensure consistent care st rs are applied across different care units.